Strategi Manajemen Yang Bertanggung jawab Pada Pengelolaan Industri Penerbitan Buku: Analisis STOP SIT di Sebuah Penerbitan Buku di Jakarta - Maria Jashinta Elisabet Hamboer (Brand Communication, 2022)
World of local book publishing get stroke with the pandemic. There were any book publishing go broke because changing of market book rightnow. Digital era and low book literacy in Indonesia give to flagg local book publishing market. This research aims to determine the marketing communication strategies of local book companies in the digital era. The research methodology is qualitative analysis using interview techniques with several existing publishing company management parties. Analysis using the STOP SIT analysis model in marketing communications. This study aims to determine the marketing communication strategies of local book companies in the digital era. The research methodology is qualitative analysis using interview techniques with several existing publishing company management parties. Analysis using the STOP SIT analysis model in marketing communications. The research findings show that responsible management is the basis for local book publishers in their efforts to gather their reading community. Choices for brand battles are still prioritized in an effort to win the digital book market. Most of the promotions and advertisements launched by local book publishers are aimed at gathering more communities to read the products they produce. Government assistance such as financial assistance, convenience in various policies to keep local publishers alive is what many people are hoping for at this time.